2013
DOI: 10.1097/qai.0b013e3182a97c39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Switching From Efavirenz to Raltegravir on Endothelial Function, Bone Mineral Metabolism, Inflammation, and Renal Function

Abstract: We performed a randomized, controlled trial in 30 HIV-infected participants to either continue tenofovir/emtricitabine/efavirenz (Continuation Group) or switch to tenofovir/emtricitabine/raltegravir (Switch Group) for 24 weeks. There were no significant differences in the changes in flow-mediated dilation, 25(OH)vitamin D, or parathyroid hormone levels. Total cholesterol, high sensitivity C-reactive protein, serum alkaline phosphatase, sCD14 levels, and renal function significantly declined in the Switch Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 32 publications
3
36
0
3
Order By: Relevance
“…[20], [21] Whether these results directly translate into changes in subclinical markers of atherosclerosis is debatable, given that switching to RAL-based regimens failed to show improvement in flow-mediated dilation. [22] Moreover, studies examining both switching to and intensification of RAL-based ART have not demonstrated any further decrease in ultrasensitive HIV-RNA detection [23], [24], leaving it difficult to hypothesize how residual viremia would fit into the association between RAL and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[20], [21] Whether these results directly translate into changes in subclinical markers of atherosclerosis is debatable, given that switching to RAL-based regimens failed to show improvement in flow-mediated dilation. [22] Moreover, studies examining both switching to and intensification of RAL-based ART have not demonstrated any further decrease in ultrasensitive HIV-RNA detection [23], [24], leaving it difficult to hypothesize how residual viremia would fit into the association between RAL and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, mice without a retroviral background, including C57BL/6 mice, did not develop proteinuria or autoimmunity over this prolonged interval. In the RAL Switch trial, 3 elevations of both serum creatinine and plasma cystatin C were observed in patients. While this finding provided an impetus for our study, we did not find an elevation of cystatin C in RAL and DTG mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse retroviral model, treatment with RAL led to increased autoimmunity manifested by hemolytic anemia and proteinuria. 4 Given these findings, we sought to determine whether a two-week regimen of 1 Division of Nephrology, Indiana University School of Medicine, Indianapolis, USA 2 Division of Clinical Pharmacology, Indiana University School of Medicine, Indianapolis, USA 3 Division of Infectious Diseases, Indiana University School of Medicine, Indianapolis, USA high-dose integrase inhibitor administration had a direct nephrotoxic effect in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…Nell'ambito degli inibitori nucleosidici/nucleotidici della transcriptasi inversa (NRTI), i dati della letteratura hanno evidenziato generalmente una riduzione dei valori di trigliceridi, colesterolo totale ed LDL sostituendo stavudina, didanosina o zidovudina con tenofovir (preferibile) o abacavir (in alternativa, se il test HLA B*5701 è negativo) (24,25). Tra gli inibitori non nucleosidici della transcriptasi inversa (NNRTI), efavirenz è associato più spesso a dislipidemia e può essere sostituito, con effetti favorevoli sui parametri lipidici, da altri NNRTI (quali nevirapina, etravirina o rilpivirina) o da un inibitore dell'integrasi (raltegravir) (26)(27)(28)(29)(30). Gli inibitori della proteasi boosterati con ritonavir (PI/r) sono i farmaci più spesso associati a ipertrigliceridemia e/o ipercolesterolemia e gli studi di switch hanno dimostrato che si può ottenere un miglioramento significativo della dislipidemia sostituendo il PI/r con un altro PI a minor impatto sull'assetto lipidico (atazanavir, atazanavir/r, darunavir/r), con un NNRTI (nevirapina, etravirina, rilpivirina) o con un inibitore dell'integrasi (raltegravir, elvitegravir/cobicistat) (31-39).…”
Section: Gestione Del Rischio Cardiovascolare: Stile DI Vita E Terapiunclassified